Morphological features of the recitation of Abu Amr ibn al-Ala’ and their role in conveying meaning - belhocine, mohamed (El Omda in Linguistics and Discourse Analysis, 2025)
The recitation of Abu Amr ibn Al-Alaa is one of the seven well-known recitations that have gained significant acceptance among scholars. It ranks third in prevalence after the recitations of Nafi and Asim, due to the fact that its author combined proficiency in recitations with mastery in grammar. In fact, he is considered one of the leading figures and authorities in the field, being a mentor to prominent scholars such as Yunus ibn Habib and Al-Khalil ibn Ahmad, among others. This makes his recitation unique and distinguished from other recitations, particularly in terms of grammar and morphology. In this research paper, I aim to highlight some of its morphological characteristics, attempting to compare them with those adopted by other reciters. The study is built around a significant research question that has troubled scholars in this field: What are the morphological phenomena that characterize the recitation of Abu Amr? And do these characteristics influence the interpretation of Quranic verses?